Dynamic ultra-high pressure homogenisation of whey protein-depleted milk concentrate. (July 2015) - Sørensen, Hanne; Mortensen, Kell; Sørland, Geir Humborstad; Larsen, Flemming Hofmann; Paulsson, Marie; Ipsen, Richard
Abstract: Effects of dynamic ultra-high pressure homogenisation (UHPH) on the micro- and macrostructure of whey protein-depleted milk concentrate solutions with different mineral concentrations (5.0, 7.5, 10.0%, w/w), pH (5.8, 6.2, 6.6) and amount of added sodium chloride (0, 1.5, 3.0%, w/w) were investigated. Significantly increased viscosity was observed in samples at pH 5.8 without added NaCl and with UHPH treatment of 300 MPa and this effect was more pronounced at low mineral level. In this sample, irrespective of mineral content, an increased particle size was also found. The lowest water mobility was observed in samples with low mineral level, low pH and no added NaCl. The results indicate that two-dimensional longitudinal-transverse relaxation nuclear magnetic resonance (NMR) measurements can contribute to a better understanding of microstructure formation in whey protein-depleted milk concentrate. Application 1 H and 31 P NMR spectroscopy indicated that UHPH treatment only affected protein aggregation and not casein micelle structure.